2020
DOI: 10.1002/mar.21350
|View full text |Cite
|
Sign up to set email alerts
|

An analysis of social media marketing strategy and performance in the context of fashion brands: The case of Taiwan

Abstract: This study examines the social media strategy and performance of fashion brands. Drawing upon the resource‐based view, the study explores the influence of entrepreneurial orientation, innovation orientation, and market orientation on social media strategy and performance. Analysis was conducted using data on 207 Taiwanese fashion brands. These data were collected from a mail survey. Structural equation modeling and fuzzy‐set qualitative comparative analysis were used to test the empirical relationships propose… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 25 publications
(32 citation statements)
references
References 59 publications
0
18
0
2
Order By: Relevance
“…It is necessary to identify the critical success factors of the social media strategy and how it affects organizational performance. To clarify these issues, Wu, Guaita-Martinez, and Martin-Martin developed a study that provides a comprehensive research framework for social media, environment, marketing strategy, and performance [23]. After analyzing 207 Taiwanese brands, the results confirmed that social media strategy is positively affected by an organization's business, market, and innovation orientation.…”
Section: Research On Fashion Marketing and Social Networkmentioning
confidence: 93%
See 1 more Smart Citation
“…It is necessary to identify the critical success factors of the social media strategy and how it affects organizational performance. To clarify these issues, Wu, Guaita-Martinez, and Martin-Martin developed a study that provides a comprehensive research framework for social media, environment, marketing strategy, and performance [23]. After analyzing 207 Taiwanese brands, the results confirmed that social media strategy is positively affected by an organization's business, market, and innovation orientation.…”
Section: Research On Fashion Marketing and Social Networkmentioning
confidence: 93%
“…Consequently, the social media strategy provides brand visibility and supports market research. Companies have the opportunity to conduct market research, communicate with their customers, and collect feedback from them [23].…”
Section: Research On Fashion Marketing and Social Networkmentioning
confidence: 99%
“…The fashion industry has developed its own manner of communication in digital media, which is a key instrument for promoting its commercialization. Therefore, social networks offer the possibility for companies to communicate with their current and potential customers publicly, which in turn allows them to carry out market research (Wu et al, 2020) and to collect comments from them, which, despite being neutral, can serve as a source of information. Therefore, another original contribution of the present work is to discover what type of brand content generates more neutral comments and contributes as a source of information: H4: Brand content influences negative comments.…”
Section: Objectives and Hypothesismentioning
confidence: 99%
“…Most past research concerning marketing strategy models has focused on the conceptualization of marketing strategy making [e.g., 10,52], the causal relationships and correlations between marketing strategy variables [e.g., 8,10,53,54], the interactions between variables [55], and the optimization of marketing strategies [56]. In comparison, relatively few studies have used MADM models to investigate the key elements of marketing strategies.…”
Section: Marketing Strategymentioning
confidence: 99%